2009
DOI: 10.1007/s12274-009-9094-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of orthorhombic LiMnO2 nano-particles and LiMnO2 nanorods and comparison of their electrochemical performances

Abstract: Orthorhombic LiMnO 2 nanoparticles and LiMnO 2 nanorods have been synthesized by hydrothermal methods. LiMnO 2 nanoparticles were synthesized by simple one-step hydrothermal method. To obtain rod-like LiMnO 2 , -MnOOH nanorods were fi rst synthesized and then the H + ions were completely replaced by Li + resulting in LiMnO 2 nanorods. Their electrochemical performances were thoroughly investigated by galvanostatic tests. Although the LiMnO 2 nanoparticles have smaller size than LiMnO 2 nanorods, the latter exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Zhou et al reported that LiMn 2 O 4 nanowires have high-rate performance with its the discharge capacity reaching 118, 108, 102, and 88 mA·h/g at rates of 0.1, 5, 10, and 20 A/g, respectively [16]. Our work has also shown that LiMnO 2 nanorods exhibited higher discharge capacity and better cyclability than LiMnO 2 nanoparticles [17]. In addition to these examples of cathode materials, similar phenomena have also been found for many anode materials, such as SnO 2 [18], Si [19], Co 3 O 4 [20], TiO 2 [21], CoSb [22].…”
Section: Introductionsupporting
confidence: 65%
“…Zhou et al reported that LiMn 2 O 4 nanowires have high-rate performance with its the discharge capacity reaching 118, 108, 102, and 88 mA·h/g at rates of 0.1, 5, 10, and 20 A/g, respectively [16]. Our work has also shown that LiMnO 2 nanorods exhibited higher discharge capacity and better cyclability than LiMnO 2 nanoparticles [17]. In addition to these examples of cathode materials, similar phenomena have also been found for many anode materials, such as SnO 2 [18], Si [19], Co 3 O 4 [20], TiO 2 [21], CoSb [22].…”
Section: Introductionsupporting
confidence: 65%
“…The increased capacity was attributed to the unique 1D morphology, through which better strain accommodation and facile Li + transport may have resulted. Early increases in capacity during electrochemical cycling however, suggests some spinel formation may have occurred although this remained unquantified in the study [288]. Capacity fade as a result of cubic spinel formation may, however, ultimately render LiMnO2 electrodes unviable candidates unless such transitions are facilitated.…”
Section: Limnxoymentioning
confidence: 83%
“…While the transition seemingly affects the initial cycling behaviour of LiMnO2, an insignificant contribution is suggested for the 5 th and subsequent cycles [287]. Recently published reports of various nanostructured Li/MnO2 architectures include nanorods/nanoparticles [288], mesoporous [289] and nanocrystalline solids [286,290,291]. For example, the hydrothermal treatment of γ-MnOOH nanorod templates with LiOH at 200 °C resulted in orthorhombic LiMnO2 nanorods which delivered a capacity of 180 mA h g -1 after 30 cycles [288].…”
Section: Limnxoymentioning
confidence: 99%
“…For example, Wan's group has calculated that a reduction of diffusion length from 10 μm (the typical particle size of commercial electrode materials) to 100 nm, results in a decrease in the mean diffusion time from 5000 to 0.5 s [14]. Many reports have also demonstrated that smaller particles of electrode materials have shorter diffusion lengths for Li + , higher electrode/electrolyte contact areas, and better accommodation of the strain than common micron-sized materials [15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%